1988
DOI: 10.1177/030089168807400615
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Carcinoid with S-100 Positive Sustentacular Cells

Abstract: A case of double bronchial typical carcinoid of the central type, with a nodal metastasis and paraneoplastic Cushing syndrome is reported. The case is remarkable because both the primary tumors and nodal metastasis were composed of a double cell population: one was arranged in nests, was argyrophilic, immunostained with PHE-5 monoclonal antibody, and contained neurosecretory granules; the other one was neither argyrophilic nor PHE-5-immunoreactive, but was strongly immunoreactive for S-100 protein, had a stell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[15][16][17][18] Studies such as these, and others, 6,[19][20][21] have revealed S100-positive sustentacular cells to be present in the great majority of appendiceal carcinoids, and a significant proportion of such tumours arising at other locations in the gastrointestinal tract also appear to contain them. [5][6][7] In 1982, Nakajima et al 22 described S100-positive sustentacular cells in a bronchial carcinoid tumour and a series of subsequent studies has confirmed the observation, 8,19,[23][24][25] a sustentacular cell component being reported in up to 55% of tumours studied. The present investigation revealed sustentacular cells to be present in a higher proportion than this.…”
Section: Discussionmentioning
confidence: 89%
“…[15][16][17][18] Studies such as these, and others, 6,[19][20][21] have revealed S100-positive sustentacular cells to be present in the great majority of appendiceal carcinoids, and a significant proportion of such tumours arising at other locations in the gastrointestinal tract also appear to contain them. [5][6][7] In 1982, Nakajima et al 22 described S100-positive sustentacular cells in a bronchial carcinoid tumour and a series of subsequent studies has confirmed the observation, 8,19,[23][24][25] a sustentacular cell component being reported in up to 55% of tumours studied. The present investigation revealed sustentacular cells to be present in a higher proportion than this.…”
Section: Discussionmentioning
confidence: 89%
“…We also found that the highest number of Sox10‐positive cells in primary sites correlated closely with that in the metastatic lymph nodes. The presence of sustentacular cells in a metastatic site has been reported previously in one case each of bronchial carcinoid tumour 15 and malignant pheochromocytoma 9 . These results indicate that sustentacular cells do not maintain the structure of tumour nests.…”
Section: Discussionmentioning
confidence: 57%
“…Using Sox10 labelling, we found sustentacular cells in TC (66.7%) and AC (58.3%) tumours but not in LCNEC or SCLC. In previous studies using immunostaining with the less‐specific S100 protein, bronchial carcinoid tumours have been found to contain from 18% to 82% sustentacular cells 3,6,11–17 . To our knowledge, there has been only one previous report that used Sox10 labelling to test for the presence of sustentacular cells in AC and TC tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation